Long-Term Clinical Investigation of the Hepatobiliary Agents: 99mTc- HIDA and 99mTC-p-Butyl-IDA - Agha, N. H.; AI-Hilli, A. M.; Dahir, N. D.; Al-Hissoni, M. S.; Jasim, M. N.; Miran, K. M.; Amira, H. Shubber (Nuklearmedizin - NuclearMedicine, 1986)
The organ distribution data for the two hepatobiliary agents HIDA and p-butyl- IDA in mice showed substantial differences in the extent and rate of hepatobiliary clearance of radioactivity. 99mTc-HIDA and 99mTc-p-butyl-IDA were used in computer assisted serial hepatobiliary scintigraphy. In normal subjects, the data of dynamic studies showed that the kidneys were no longer seen after 2.5 min with p-butyl-IDA. Liver radioactivity decreased significantly after 10 min with HIDA compared to 35 min with p-butyl-IDA. The gall bladder was always visualized at the 10-12th min and the 25-30th min with HIDA and p-butyl-IDA respectively. 99mTc-HIDA provided superior hepatic duct images.Die Organverteilung der beiden hepatobiliären Agenzien HIDA und p-butyl-IDA wiesen bei der Maus erhebliche Unterschiede in Ausmaß und Schnelligkeit der hepatobiliären Radioaktivitätsclearance auf. 99mTc- HIDA und 99mTc-p-butyl-IDA wurden für die computerunterstützte hepatobiliäre Sequenzszintigraphie eingesetzt. Bei Normalpersonen zeigte die dynamische Studie, daß die Nieren mit p-butyl-IDA nach 2.5 min nicht mehr sichtbar waren. Die Radioaktivität in Leberparenchymen nahm signifikant ab der 10, min bei HIDA und ab der 35. min bei p-butyl-IDA ab. Die Gallenblase wurde immer zwischen der 10.-12. min und 25.-30. min mit HIDA bzw. p-butyl- IDA dargestellt. Eine bessere Darstellung der Gallenwege war mit 99mTc-HIDA gewährleistet.revised form: April 25, 1986